2013
DOI: 10.1038/gene.2013.15
|View full text |Cite
|
Sign up to set email alerts
|

CCR5-Δ32 genotype does not improve predictive value of IL28B polymorphisms for treatment response in chronic HCV infection

Abstract: Abbreviations: ALT, alanine aminotransferase; GGT, gamma glutamyltransferase; HCV, hepatitis C virus; IFN, interferon; SVR, sustained virological response. CCR5-∆32 and IL28B polymorphisms in treatment of HCV infectionPage 4 of 24 AbstractBackground: IL28B polymorphisms strongly predict spontaneous and treatment-induced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our results show that this CCR5 polymorphism did not play any significant role in the anti-HCV treatment response, while at the same time confirming the very well known role played by severe fibrosis, older age, higher pretreatment HCV RNA, genotype 2 and 3 and IFNL3/4 genetic polymorphisms. As already known, the latter are currently the strongest host genetic markers to predict IFN-alpha-based treatment-induced HCV clearance, and, as demonstrated in a recent and large serie of 813 Caucasian patients with chronic hepatitis C genotype 1 [27], CCR5delta32 did not improve prediction of SVR in the context of the IFNL3 polymorphisms. These results match those of previous, smaller series [28][31], but appear in conflict with those of an early study which had identified CCR5delta32 carriage as an independent negative predictor for the end of treatment virological response to the less potent IFN-alpha monotherapy [30].…”
Section: Discussionmentioning
confidence: 91%
“…Our results show that this CCR5 polymorphism did not play any significant role in the anti-HCV treatment response, while at the same time confirming the very well known role played by severe fibrosis, older age, higher pretreatment HCV RNA, genotype 2 and 3 and IFNL3/4 genetic polymorphisms. As already known, the latter are currently the strongest host genetic markers to predict IFN-alpha-based treatment-induced HCV clearance, and, as demonstrated in a recent and large serie of 813 Caucasian patients with chronic hepatitis C genotype 1 [27], CCR5delta32 did not improve prediction of SVR in the context of the IFNL3 polymorphisms. These results match those of previous, smaller series [28][31], but appear in conflict with those of an early study which had identified CCR5delta32 carriage as an independent negative predictor for the end of treatment virological response to the less potent IFN-alpha monotherapy [30].…”
Section: Discussionmentioning
confidence: 91%